2008
DOI: 10.1016/j.freeradbiomed.2008.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effect of SIN-1 is reliant upon cardiomyocyte contractile state

Abstract: Many studies have demonstrated a biphasic effect of peroxynitrite in the myocardium, but few studies have investigated this biphasic effect on β-adrenergic responsiveness and its dependence on contractile state. We have previously shown that high SIN-1 (source of peroxynitrite, 200 μmol/L) produced significant anti-adrenergic effects during maximal β-adrenergic stimulation in cardiomyocytes. In the current study, we hypothesize that the negative effects of high SIN-1 will be greatest during high contractile st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 41 publications
2
26
0
1
Order By: Relevance
“…These data are consistent with our previous study that showed that low levels of exogenous peroxynitrite (produced from SIN-1) increased basal Ca 2ϩ transient and shortening amplitude in murine myocytes. Interestingly, similar to NOS1 inhibition, the contractile effects of SIN-1 were absent in PLB Ϫ/Ϫ myocytes (22). However, it still remains to be determined whether NO itself or other reactive nitrogen species are also part of the NOS1 signaling pathway.…”
Section: Discussionmentioning
confidence: 91%
“…These data are consistent with our previous study that showed that low levels of exogenous peroxynitrite (produced from SIN-1) increased basal Ca 2ϩ transient and shortening amplitude in murine myocytes. Interestingly, similar to NOS1 inhibition, the contractile effects of SIN-1 were absent in PLB Ϫ/Ϫ myocytes (22). However, it still remains to be determined whether NO itself or other reactive nitrogen species are also part of the NOS1 signaling pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, it was reported that 10 µmol/L SIN-1 would correspond to 3 nmol/L of peroxynitrite and thus represent physiological rather than pathological conditions [48]. Furthermore, the differences in the total (175% increase at 15 min) and protein-specific (significant increase at 30 min) carbonylation suggested that compared to proteins, lipids might be the primary targets of ROS/RNS.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of carbon dioxide (CO 2 ) peroxynitrite anion forms nitroso-peroxocarbonate (ONOOCO 2 - ), which in turn decomposes to • NO 2 , CO 3 - and NO 3 - [47]. We and others have previously demonstrated the complex nitroxidative effect of SIN-1 treatment in cell culture models [46], [48], [49], [50]. Here, free radical production in SIN-1-treated (10 µmol/L) CM was monitored by DCFDA assay (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…But, similar to ROS, may also modulate the activity of various kinases and phosphatases to change the protein phosphorylation status. We have previously shown that a peroxynitrite donor (SIN-1) in a low dose was able to increase PLB Serine16 phosphorylation via activation of PKA (96,97). Surprisingly, the peroxynitrite-mediated increase in PKA activity occurred in the absence of cAMP, and most likely occurs via Snitrosylation (28).…”
Section: Nitroso-redox Imbalance In Hf 2049mentioning
confidence: 92%